2022
DOI: 10.1007/s00397-022-01338-z
|View full text |Cite
|
Sign up to set email alerts
|

Rheological behavior of gel polymer electrolytes: yield stress and viscoelasticity

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…In order to have reproducible results, a slurry preparation protocol is followed to produce each of the samples before either rheology or electrochemical characterization. Slurry composition was taken from a previous study using the same experimental set-up (Choi et al 2020a), except for gelling agents presented in a previous study (Milián et al 2022 Germany) and ZnO (Alfa Aesar, United States) was added to the solution. The sample was mixed using a high shear homogenizer Ultra Turrax T25 (Ika, Germany) at a speed of 11 000 rpm for 1 minute to disperse the clay particles, thickening the mixture and forming a gel.…”
Section: Slurry Preparationmentioning
confidence: 99%
See 4 more Smart Citations
“…In order to have reproducible results, a slurry preparation protocol is followed to produce each of the samples before either rheology or electrochemical characterization. Slurry composition was taken from a previous study using the same experimental set-up (Choi et al 2020a), except for gelling agents presented in a previous study (Milián et al 2022 Germany) and ZnO (Alfa Aesar, United States) was added to the solution. The sample was mixed using a high shear homogenizer Ultra Turrax T25 (Ika, Germany) at a speed of 11 000 rpm for 1 minute to disperse the clay particles, thickening the mixture and forming a gel.…”
Section: Slurry Preparationmentioning
confidence: 99%
“…GPEs composition together with their rheological characterization can be found in (Milián et al 2022), where is reported that all GPEs were found to have a yield stress fluid behavior.…”
Section: Slurry Preparationmentioning
confidence: 99%
See 3 more Smart Citations